Fishing for Ghanaians only - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A new law in Ghana now reserves trawling for fish in territorial waters for Ghanaians only. The law also stipulates that 50% of investment in tuna fishing (previously 25%) is reserved for Ghanaians, while foreigners may invest in the remaining 50%....